Nutritional improvement of ensiled rice straw through supplementation of urea, molasses, soybean seed meal and aquatic plants - MALEK, M A; KHAN, M J (The Indian Journal of Animal Sciences, 2011)
A study was conducted to assess the effectiveness of ensiling rice straw with urea (4%), molasses (2%), soybean meal (4%) and supplementation with aquatic plants viz. water hyacinth (Eichhornia crassipes), Azolla (Azolla pinnata) and two varieties of duck weeds (LT-Lemna trisulaca and LP-Lemna perpusila) on nutritive value. Proximate composition, NH3-N production, energy value, organic matter digestibility (OMD) and in situ disappearance of dry matter (DM) and crude protein (CP) were studied. Crude protein, organic matter (OM), ether extract (EE), metabolizable energy (ME) and in sacco degradability of DM and CP increased progressively with increased level of aquatic plants. Ensiling straw with supplementation of 25% water hyacinth (WH) or azolla (AZ) or duck weeds results in an increase in CP content from 12.2 to 18.7, OM 88.3 to 89.5, EE 3.1 to 4.1, NFE 38.2 to 44.3, ash 10.5 to 11.7 and decreased CF content from 29.7 to 27.40/0. Supplementation improved (P